Sex-Related Differences in Outcomes of Endovascular Treatment for Anterior Circulation Large Vessel Occlusion. Issue 2 (24th January 2023) - Sun, Dapeng; Raynald; Huo, Xiaochuan; Jia, Baixue; Tong, Xu; Ma, Gaoting; Wang, Anxin; Ma, Ning; Gao, Feng; Mo, Dapeng; Nguyen, Thanh N.; Miao, Zhongrong; et al.
Abstract : Background: Sex disparities in acute large vessel occlusion (LVO) following endovascular treatment (EVT) have been recently reported. However, there is uncertainty about the effect of sex differences on functional outcomes after EVT, particularly in an Asian population. The present study aimed to compare the clinical and safety outcomes between men and women with anterior circulation LVO treated with EVT. Methods: We analyzed data from the ANGEL-ACT (Endovascular Treatment Key Technique and Emergency Work Flow Improvement of Acute Ischemic Stroke: a Prospective Multicenter Registry Study) Registry, which was conducted at 111 hospitals from 26 provinces in China between November 2017 and March 2019. Men and women with anterior circulation LVO treated with EVT were matched using propensity scores. After a 1:1 propensity score matching, we compared the clinical outcomes including 90-day ordinal modified Rankin Scale distribution (primary outcome), procedure duration, successful reperfusion, symptomatic intracranial hemorrhage, and mortality. Furthermore, we explored sex modification on the primary outcome in subgroup analysis. Results: Of 1321 patients, 483 (36.6%) were women and 838 (63.4%) were men. The mean age for women and men were 68 and 62 years old, respectively. Among 578 patients identified after matching, there were no sex differences (men versus women) in 90-day ordinal modified Rankin Scale distribution (median [interquartile range], 4 [1–5] versus 3 [1–5], P =0.464), successful reperfusion (86.5% versus 91.0%, P =0.089), symptomatic intracranial hemorrhage (6.5% versus 7.9%, P =0.512), and mortality within 90 days (17.7% versus 17.0%, P =0.826). However, men had a longer median procedure duration than women (86 [52–128] versus 72 [48–110] minutes, β=14.51, [95% CI, 4.19–24.84]; P =0.006). Subgroup analysis showed that in patients with National Institutes of Health Stroke Scale score <15, women tended to have a better outcome than men, whereas there was no gender effect in those with National Institutes of Health Stroke Scale score ≥15 ( P for interaction=0.032). Conclusions: Overall, this matched-control study from the ANGEL-ACT study showed similar clinical outcomes between men and women with anterior circulation LVO treated with EVT. However, in the subgroup of patients presenting with lower stroke severity (ie, National Institutes of Health Stroke Scale score <15), women tended to have a better outcome than men highlighting a potential sex disparity for further investigation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03370939.